Psychometric properties of the Sport Courage Scale for Chinese athletes - Gao, Shenmao; Guo, Zeyou; Zhang, Renfang; Jin, Junze; Dou, Guangbo (Frontiers in Psychology, 2023)
Objective To revise Sport Courage Scale (SCS) suitable for Chinese athletes. Methods Six hundred and eighty three athletes were selected for verification factor analysis, correlation analysis, reliability analysis, and independent sample t-test using the method of random sampling of the entire group. Results Confirmatory factor analysis model showed that model 1 (25 items) failed to fit the data; while model 2 (20 items) was finally accepted with its five-factor model. The factor structure consists of 5 dimensions (χ2/df = 2.262;CFI = 0.969;TLI = 0.963; RMSEA = 0.043; SRMR = 0.044). Cronbach’s α of the final version of SCS was 0.845, and the corrected correlation coefficient between the items and the total score of the scale was between 0.352 and 0.788. Conclusion Revised SCS has good reliability and validity and can be used as a measurement tool for the sports courage of athletes in China.